Carryover effects of calibration to visual and proprioceptive information on near field distance judgments in 3D user interaction - Ebrahimi, Elham; Altenhoff, Bliss M.; Pagano, Christopher C.; Babu, Sabarish V. (3DUI, proceedings : 2015 IEEE Symposium on 3D User Interfaces : Arles, France, 23-24 March, 2015, 2015)
It has been suggested that closed-loop feedback of travel and locomotion in an Immersive Virtual Environment (IVE) can overcome compression of visually perceived depth in medium field distances in the virtual world [15, 21]. However, very few experiments have examined in IVEs the carryover effects of multisensory feedback during manual dexterous 3D user interaction in overcoming distortions in near-field or interaction space depth perception, and the relative importance of visual and proprioceptive information in calibrating users distance judgments. We report the results of an empirical evaluation to examine the carryover effects of calibrations to one of three perturbations of visual and proprioceptive feedback: i) Minus condition (-20% gain) in which a visual stylus appeared at 80% of the distance of a physical stylus, ii) Neutral condition (0% gain) in which a visual stylus was co-located with a physical stylus, and iii) Plus condition (+20% gain) in which the visual stylus appeared at 120% of the distance of the physical stylus. In between subjects design, participants provided manual reaching distance estimates during three sessions; a baseline measure without feedback (open-loop distance estimation), a calibration session with visual and proprioceptive feedback (closed-loop distance estimation), and a post-interaction session without feedback (open-loop distance estimation). Feedback was shown to calibrate distance judgments quickly within an IVE, with estimates being farthest after calibrating to visual information appearing nearer (Minus condition), and nearest after calibrating to visual information appearing further (Plus condition).